THE USE OF BIOCHAR FOR IMPROVE SOIL PROPERTIES AND GROWTH OF PADDY IN PEATLAND - Maftuah, Eni; Indrayati, Linda (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2013)
The main constraint in the management of peatlands include: high soil acidity, very low of nutrient availability especially NPK. The study aimed to determine the role of biochar to improve soil properties and paddy growth in peatlands. The study conducted in Landasan Ulin rural, Gambut district, Banjar regency, South Kalimantan. The study was conducted from June to October 2012. Research arranged in a randomized block design, with three replications. The treatment given was a combination of the type and dose of ameliorant i.e. the 3 types of ameliorant: F1 (50% purun tikus grass + 50% agricultural weed), F2 (16.7% chicken manure + biochar 83.3%), F3 (9% chicken manure + 91% purun tikus grass), with a dose of 2.5, 5 and 7.5 t ha-1 and control. The results showed that treatment of biochar could to increase soil pH, total N, and exchangable P (Bray I) though not significant, and significant in increasing the exchangable K compared to controls. On the growth of rice plants giving biochar can increase plant height, number of tillers and number of panicles compared to controls. Key words: biochar, improve of soil properties, peat, growth, paddy